The Comparison Of Chest X-Ray Changes Between Post-Covid-19-Infection Patients With Mild-Moderate Severity And Severe-Critical Severity At Ugm Academic Hospital - Nadira Adristi Amaradinka; Siswanto; Henda Ageng Rasena; Roihan Mohamad Iqbal; Rahmaningsih Mara Sabirin; Rakhmat Ari Wibowo; Dwi Damar Andriyani (International Journal of Radiology and Imaging, 2023)
Introduction: Post-COVID-19 syndrome can be seen from the radiological findings on the chest X-ray (CXR). However, limited studies compared CXR changes in post-COVID-19 patients based on their severity.  Methods: Thirty-three post-hospitalized COVID-19 patients who came to the Long COVID Clinic at UGM Academic Hospital were divided into mild-moderate and severe-critical groups. The CXR were taken during hospital admission, in the 4th week, and in the 8th week. CXR images were assessed with the Brixia Score method. Results: The Brixia score in the mild-moderate group (n = 17) and severe-critical (n = 16) group showed a trend of change, which increased in the 4th week and decreased in the 8th week. However, there were no significant changes between the two groups during hospital admission, in the 4th week, and in the 8th week. The Brixia score during hospital admission and in the 8th-week follow-up in the mild-moderate group was significantly lower than that of the severe-critical group. Clinically, the mean Brixia score in the mild-moderate group ranges from mild pneumonia, while the severe-critical group ranges from moderate pneumonia. Conclusion: There is no significant resolution of the CXR until the 8th-week follow-up in post-COVID-19 infection patients with mild-moderate and severe-critical severity. However, the CXR during hospital admission and the 8th week is better in post-COVID-19 infection patients with mild-moderate severity. Keywords: chest X-ray, COVID-19, infectious disease, post-COVID-19 syndrome, severity,